Influence of Teachers’ Professional Knowledge on Students’ Academic Performance in Senior Secondary Schools, North Central, Nigeria - Madu Christian Onyekachi (Journal of Research in Innovative Teaching and Inclusive Learning, 2026)
This study investigated the influence of teachers’ professional knowledge on students’ academic performance in public secondary schools in North Central, Nigeria. Specifically, the study examined how teachers' compliance with knowledge correlates with students’ academic performance. The study was guided by two research questions and one null hypothesis. The descriptive and expo factor research design was adopted for the study, with a sample consisting of 30 teachers from 30 selected public secondary schools in North Central Nigeria. The samples were chosen following a multistage sampling technique. Two instruments were used to collect data for this study: the Teachers Compliance with Professional Knowledge Questionnaire (TCPKQ) and the Students Academic Performance Proforma (SAPP). The face and content validity of the instrument were ascertained. The instrument was subjected to a trial test, and a reliability coefficient of 0.98 was obtained for TCPKQ using the Cronbach Alpha. Mean and standard deviation were used to answer the research questions, while linear Regression Analysis was used to test the hypotheses at a 0.05 level of significance. The findings revealed a significant positive relationship between teachers' knowledge and students’ academic performance. The study recommended, among others, that principals should collaborate with other professional bodies to organize intensive and regular seminars and workshops for the capacity development of teachers to enhance professional knowledge and quality teaching and learning processes in secondary schools.